2014
DOI: 10.1002/pc.23011
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional silica/lignin hybrid material as a potential bio-based polypropylene filler

Abstract: A functional silica/lignin hybrid filler was obtained using a process of mechanical grinding of precursors (Syloid®244 silica and kraft lignin). The product underwent comprehensive physicochemical and dispersive–morphological analysis. The silica/lignin hybrid has good homogeneity and a surface area of 164 m2/g. The effectiveness of combination was confirmed by Fourier transform infrared spectroscopy and elemental analysis. The high electrokinetic stability (over almost the whole of the analyzed pH range) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 54 publications
20
78
0
2
Order By: Relevance
“…The high interest for these materials is the effective surface of the nanosized filler making it possible to tailor and handle the properties of the material with very small proportions of the filler. The present work is the continuation of our earlier studies [43] on novel functional silica/lignin hybrid material as a potential bio-based polypropylene filler. In a preliminary study, we showed that the incorporation of silica/lignin hybrid filler influences on elongation at break and impact strength.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…The high interest for these materials is the effective surface of the nanosized filler making it possible to tailor and handle the properties of the material with very small proportions of the filler. The present work is the continuation of our earlier studies [43] on novel functional silica/lignin hybrid material as a potential bio-based polypropylene filler. In a preliminary study, we showed that the incorporation of silica/lignin hybrid filler influences on elongation at break and impact strength.…”
Section: Introductionmentioning
confidence: 48%
“…Silica with its good mechanical and thermal resistance can form interesting combination with cheap and environmentally friendly lignin. New hybrid materials may be used as functional biosorbents [41,42] and also as polymer fillers [43]. The high interest for these materials is the effective surface of the nanosized filler making it possible to tailor and handle the properties of the material with very small proportions of the filler.…”
Section: Introductionmentioning
confidence: 99%
“…Obtained results indicate that due to porous structure properties produced hybrid fillers are active by means of physical. Analysis of the TG curves of hybrid filler (SiO 2 /lignin ratio 5:1) as well as its precursors is presented in our previous work [33]. However, it should be brought up that the hybrid filler was characterized by very good thermal properties.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of functional hybrid filler combining mechanical and thermal properties of inorganic silica with availability and low-cost organic lignin gains more interest these days [33,34]. The resulting hybrid materials could be used as polymer fillers or biosorbents [33,35,36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation